2020
DOI: 10.4102/sajhivmed.v21i1.1123
|View full text |Cite
|
Sign up to set email alerts
|

Cervical human papillomavirus prevalence, risk factors and outcomes in a cohort of HIV-infected women in Harare, Zimbabwe

Abstract: Background: Human papillomavirus (HPV) associated invasive cervical cancer (ICC) is common in Zimbabwe, disproportionately affecting women living with HIV (WLHIV). Understanding high-risk HPV (hrHPV) infection in relation to cervical disease is important for ICC prevention amongst WLHIV.Objectives: To describe the prevalence of cervical hrHPV, type distribution, associated risk factors and ICC screening outcomes in an urban cohort of Zimbabwean women.Methods: In this cohort study, WLHIV were tested for hrHPV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
3
1
1
Order By: Relevance
“… 21 , 22 It also highlights the important role of cervical cancer screening programs to reduce the incidence of cervical cancer. 23 , 24 Furthermore, consistent with other studies, our results showed that initiating ART at higher CD4 cell counts reduced the overall risk of developing cancer. 25 , 26 Enhanced efforts toward HIV testing and early ART initiation as prescribed in the WHO “test‐and‐treat” drive is likely to reduce cancer incidence among PLWH.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 21 , 22 It also highlights the important role of cervical cancer screening programs to reduce the incidence of cervical cancer. 23 , 24 Furthermore, consistent with other studies, our results showed that initiating ART at higher CD4 cell counts reduced the overall risk of developing cancer. 25 , 26 Enhanced efforts toward HIV testing and early ART initiation as prescribed in the WHO “test‐and‐treat” drive is likely to reduce cancer incidence among PLWH.…”
Section: Discussionsupporting
confidence: 92%
“…21,22 It also highlights the important role of cervical cancer screening programs to reduce the incidence of cervical cancer. 23,24 Furthermore, consistent with other studies, our results showed that initiating ART at higher CD4 cell counts reduced the overall risk of developing cancer. 25,26…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of hr-HPV from the current study is higher than the (19.6%) that found among WLWH in cervical cancer screening centers in Ogun and Lagos states, Nigeria [30] and antiretroviral clinic of the Federal Medical Center (36%), Keffi, Nigeria [31]. In Zimbabwe [32], also reported about 25% hr-HPV prevalence which is also lower than the findings from this study. Some other SSA countries such as Burundi, 45.7% [33], Kenya 47% [34] and 64% [35] have been reported.…”
Section: Discussioncontrasting
confidence: 89%
“…This is also in agreement with [30] where lower prevalence of hr-HPV was found among HIV infected women using ART in Nigeria. Other evidence supporting the influence of ART on cytology have been found in Nigeria [48] and Zimbabwe [32].…”
Section: Plos Onementioning
confidence: 83%